Aspects of early Greek and Babylonian hymnic poetry - Metcalf, C (2013)
This thesis is a case study of early Greek poetry in comparison to the literature of the ancient Near East, especially Mesopotamia, based on a selection of hymns (or: songs in praise of gods) mainly in Sumerian, Akkadian, Hittite and Greek. Chapters 1–3 present the core groups of primary sources from the ancient Near East: Old Babylonian Sumerian, Old Babylonian Akkadian, Hittite. The aim of these chapters is to analyse the main features of style and content of Sumerian and Akkadian hymnic poetry, and to show how certain compositions were translated and adapted beyond Mesopotamia (such as in Hittite). Chapter 4 contains introductory remarks on early Greek hymnic poetry accompanied by some initial comparative observations. On the basis of the primary sources presented in Chapters 1–4, the second half of the thesis investigates selected elements of form and content in a comparative perspective: hymnic openings (Chapter 5), negative predication (Chapter 6), the birth of Aphrodite in the Theogony of Hesiod (Chapter 7), and the origins and development of a phrase in Hittite prayers and the Iliad of Homer (Chapter 8). The conclusion of Chapters 4–6 is that, in terms of form and style, early Greek hymns were probably not indebted to ancient Near Eastern models. This contradicts some current thinking in Classical scholarship, according to which Near Eastern influence was pervasive in early Greek poetry in general. Chapters 7–8 argue that such influence may nevertheless be perceived in certain closely defined instances, particularly where supplementary evidence from other ancient sources is available, and where the extant sources permit a reconstruction of the process of translation and adaptation. Hence this thesis seeks to contribute to the current debate on early Greek and ancient Near Eastern literature with a detailed analysis of a selected group of primary sources.